Pengaruh Brand Trust, Brand Image, Brand Awareness Dan Gaya Hidup Hedonis Terhadap Keputusan Pembelian Produk Starbucks Di Kota Malang. - Halifah, Nur; Rizal, Mohammad; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study examines the impact of Brand Trust, Brand Image, Brand Awareness, and Hedonic Lifestyle on Starbucks purchase decisions in Malang City. Using Malhotra’s formula, 95 respondents were selected through purposive sampling. Data were collected via questionnaires and analyzed with SPSS 29, employing validity, reliability, normality, classical assumption tests, multiple linear regression, F-test, t-test, and R² test. Results show that Brand Trust has no effect on purchase decisions, while Brand Image, Brand Awareness, and Hedonic Lifestyle have a positive and significant influence. Keywords: Brand Trust, Brand Image, Brand Awareness, Hedonic Lifestyle, Purchase Decision